A Cu-Sn bimetallic catalyst for water electrolysis and preparation method thereof
The Cu-Sn bimetallic catalyst prepared by electrospinning technology solves the shortcomings of the existing electrolytic water catalyst in catalytic effect. By stabilizing the formation of residual oxygen and induced oxygen vacancies, catalytic activity and charge transfer efficiency are significantly improved.
Patent Information
- Application Number
- CN202411855697.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Existing electrolytic water catalysts cannot meet the needs in terms of catalytic effects, especially in overcoming high thermodynamic barriers and slow reaction kinetics.
The precursor containing copper, tin and palladium was mixed with the spinning material by electrospinning technology, and then calcined on the substrate to prepare a catalyst for electrolyzing water. The catalyst stabilizes residual oxygen and induces the formation of oxygen vacancies through specific molar ratios and calcination conditions, thereby improving catalytic activity.
In electrolyzed water, the Cu-Sn bimetallic catalyst significantly improves the catalytic activity, reduces the thermodynamic barriers of the reaction, enhances the charge transfer efficiency, and achieves excellent catalytic effects.
Smart Images

Figure CN119307959B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts, and in particular relates to a Cu-Sn bimetallic catalyst for water electrolysis and a preparation method thereof. Background Art
[0002] With the growing demand for sustainable energy, water electrolysis has attracted widespread attention as an efficient and clean way to produce hydrogen. The water electrolysis reaction consists of oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), and the efficiency of OER and HER is directly related to the energy consumption of the entire process.
[0003] In order to improve the activity of the catalyst, researchers have explored a variety of strategies, and the core optimization methods involve electronic structure regulation and active site enhancement. The specific strategies are summarized as follows: 1. Element doping, by adjusting the electronic structure of the catalyst material, the catalytic activity is directly improved. This method uses the characteristics of different elements to optimize the intrinsic performance; 2. Oxygen vacancy generation, activating the originally inert active sites, and enhancing the catalytic effect by increasing the number of oxygen vacancies. This is achieved through methods such as H2 / NaBH4 reduction; 3. Structural regulation, by adjusting the process and other means to increase the specific surface area of the catalyst and increase the catalytic active sites, such as electrospinning and electrodeposition. Although this type of doping technology has shown certain results, it faces limitations in significantly improving catalytic performance, suggesting the need to explore more efficient element doping paths.
[0004] Cu-Sn bimetallic catalysts are commonly used electrocatalytic carbon dioxide reduction reaction (CO2RR) catalysts, mainly used to catalyze the reaction to produce CO gas. Cu-Sn alloy electrocatalysts can control the selectivity of CO2RR by adjusting the binding energy of intermediates. However, compared with CO2RR, water electrolysis involves a multi-electron and multi-proton transfer process, which has higher thermodynamic barriers and slower reaction kinetics and requires a higher overpotential. There is currently no report on the application of Cu-Sn bimetallic catalysts in water electrolysis. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defect that the catalytic effect of the existing water electrolysis catalyst cannot meet the needs, thereby providing a Cu-Sn bimetallic catalyst for water electrolysis and a preparation method thereof.
[0006] To this end, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention protects a method for preparing a Cu-Sn bimetallic catalyst for electrolysis of water, wherein the preparation method comprises the following steps:
[0008] A copper-containing precursor, a tin-containing precursor, a palladium-containing precursor, a spinning material and a solvent are mixed, and electrospinning is performed, and the electrospinning product is placed on a substrate for calcination to obtain a Cu-Sn bimetallic catalyst for water electrolysis;
[0009] Among them, the molar ratio of copper element in the copper-containing precursor, tin element in the tin-containing precursor, and palladium element in the palladium-containing precursor is (2-8):(2-8):(0-4).
[0010] In the present invention, the solvent is a conventional electrospinning solvent in the art. Typically, but not limitedly, the solvent is dimethylformamide (DMF). The ratio of the solvent to the spinning material is (2-10) mL: (0.5-10) g.
[0011] In the present invention, the electrospun product and the substrate are calcined in a muffle furnace. Typically, but not limited to, the substrate is nickel foam. In the final catalyst, the nickel foam is loaded with 5-8 mg / cm 2 Active component refers to a substance containing a metal component that can play a catalytic role.
[0012] According to the present invention, the molar ratio of the copper element in the copper-containing precursor, the tin element in the tin-containing precursor, and the palladium element in the palladium-containing precursor is (5-7):(5-7):(1-3).
[0013] According to the present invention, the ratio of the copper element to the spinning material in the copper-containing precursor is (5-7) mmol: (0.5-10) g.
[0014] According to the present invention, the copper-containing precursor is a soluble copper salt.
[0015] According to the present invention, the tin-containing precursor is a soluble tin salt.
[0016] According to the present invention, the palladium-containing precursor is a soluble palladium salt.
[0017] According to the present invention, the spinning material comprises polyacrylonitrile.
[0018] According to the present invention, the soluble copper salt includes at least one of copper nitrate, copper acetate, copper chloride and copper sulfate.
[0019] According to the present invention, the soluble tin salt comprises at least one of tin alkyl sulfonate and tin chloride.
[0020] In the present invention, the alkyl tin sulfonate includes at least one of tin methyl sulfonate and tin ethyl sulfonate.
[0021] According to the present invention, the soluble palladium salt includes at least one of palladium chloride and palladium nitrate.
[0022] According to the present invention, the spinning material further comprises at least one of styrene-acrylonitrile copolymer and polyvinyl pyrrolidone.
[0023] According to the present invention, the mass ratio of polyacrylonitrile, styrene-acrylonitrile copolymer and polyvinyl pyrrolidone is (0.5-4):(0.1-4):(0.1-4).
[0024] In the present invention, the order of adding the spinning materials is the conventional order in the art, and polyacrylonitrile, styrene-acrylonitrile copolymer, and polyvinyl pyrrolidone can be added simultaneously, or polyacrylonitrile and styrene-acrylonitrile copolymer can be added first, and then polyvinyl pyrrolidone is added; wherein the weight average molecular weight of polyacrylonitrile is 30000-40000 g / mol, the weight average molecular weight of styrene-acrylonitrile copolymer is 50000-60000 g / mol, and the weight average molecular weight of polyvinyl pyrrolidone is 360000-400000 g / mol.
[0025] According to the present invention, the electrospinning comprises the following steps: loading the mixed spinning reaction liquid into the syringe of the electrospinning device, setting the electrospinning voltage, adjusting the distance between the nozzle and the collector, controlling the speed of the injection pump, and performing electrospinning.
[0026] In the present invention, the electrospinning device is a conventional device. Typically, but not limiting, the electrospinning device is a coaxial electrospinning device, the syringe is a Luer lock syringe, and the collector is an aluminum foil. Furthermore, during electrospinning, the electrospinning reaction liquid is mixed. The mixing is not limited, and it is sufficient to mix evenly.
[0027] According to the present invention, the parameters of electrospinning include: voltage of 10-40 kV, distance between nozzle and collector of 5-20 cm, injection pump pressing speed of 0.5-10 mL·h -1 ; Further, the voltage is 15-30 kV, the distance between the nozzle and the collector is 10-15 cm, and the injection pump pressing speed is 3-6 mL·h -1 .
[0028] According to the present invention, the calcination conditions include: 1-8 ° C. min -1 The temperature is raised to 300-1200℃ and calcined for 1-10h; further, the temperature is raised to 2-6℃·min -1 The temperature is raised to 500-800°C and calcined for 2-8h.
[0029] According to the present invention, the calcination atmosphere is an inert gas, typically but not limitedly, the inert gas is Ar.
[0030] The second aspect of the present invention protects a Cu-Sn bimetallic catalyst for water electrolysis prepared by the aforementioned preparation method.
[0031] The technical solution of the present invention has the following advantages:
[0032] 1. The present invention provides a method for preparing a Cu-Sn bimetallic catalyst for electrolysis of water, wherein the preparation method comprises the following steps: mixing a copper-containing precursor, a tin-containing precursor, a palladium-containing precursor, a spinning material and a solvent, electrospinning, placing the electrospinning product on a substrate for calcining, and obtaining a Cu-Sn bimetallic catalyst for electrolysis of water; wherein the molar ratio of the copper element in the copper-containing precursor, the tin element in the tin-containing precursor, and the palladium element in the palladium-containing precursor is (2-8):(2-8):(0-4); in the electrolysis of water, the residual oxygen is stabilized by the synergistic effect of the specific amount of copper element and the tin element, and the catalyst is induced to generate oxygen vacancies, the number of oxygen vacancies in the catalyst is increased, the charge transfer is promoted, and the reaction path of the electrolysis of water is guided, so that the catalyst has an excellent catalytic effect when catalyzing the electrolysis of water.
[0033] 2. In the present invention, the addition of a palladium-containing precursor can further adjust the microstructure of the catalyst, increase the number of oxygen vacancies in the catalyst, and enhance the interaction between the metal and the carrier.
[0034] 3. In the present invention, the specific dosage of copper in the copper-containing precursor, tin in the tin-containing precursor, and palladium in the palladium-containing precursor, the specific conditions for electrospinning, and the specific conditions for calcination can further improve the catalytic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 Scanning electron microscope image of the Cu-Sn bimetallic catalyst in Example 1 magnified 30,000 times;
[0037] Figure 2 Scanning electron microscope image of the Cu-Sn bimetallic catalyst in Example 2 magnified 15,000 times;
[0038] Figure 3 Electron paramagnetic resonance test graphs of the Cu-Sn bimetallic catalysts of Example 1 and Example 2;
[0039] Figure 4A graph showing the change in current density of the Cu-Sn bimetallic catalyst according to Example 1 as a function of potential;
[0040] Figure 5 A graph showing the current density of the Cu-Sn bimetallic catalyst of Example 2 as a function of potential. DETAILED DESCRIPTION
[0041] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0042] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0043] The weight average molecular weight of polyacrylonitrile (PAN) is 30,000 g / mol;
[0044] The weight average molecular weight of styrene-acrylonitrile copolymer (SAN) is 50,000 g / mol;
[0045] The weight average molecular weight of polyvinylpyrrolidone (PVP) is 360,000 g / mol.
[0046] Example 1
[0047] This embodiment provides a method for preparing a Cu-Sn bimetallic catalyst for water electrolysis, comprising the following steps:
[0048] 8 mL of DMF was used as solvent, 1.2 g of PAN, 2 g of SAN, 5 mmol of copper nitrate, 5 mmol of tin chloride and 1 mmol of palladium nitrate were added, and finally 1 g of PVP was added. After being dissolved evenly, an electrospinning reaction solution was obtained. The electrospinning reaction solution was loaded into a Luer lock syringe, and the electrospinning voltage was set to 17 kV, the distance between the nozzle and the aluminum foil was set to 15 cm, and the injection pump pressing speed was set to 1 mL·h -1 , coaxial electrospinning was performed; the electrospun product and an appropriate amount of nickel foam were placed in a muffle furnace under an inert atmosphere of Ar at 4 °C·min -1 The temperature was raised to 700 °C and calcined for 4 h to obtain a Cu-Sn bimetallic catalyst with a loading of 5 mg / cm 2 Active ingredient;
[0049] Figure 130,000 times magnified scanning electron microscope image of the Cu-Sn bimetallic catalyst in Example 1 is shown in FIG. 1 , from which it can be seen that the Cu-Sn bimetallic catalyst is a nanosheet structure.
[0050] Example 2
[0051] This embodiment provides a method for preparing a Cu-Sn bimetallic catalyst for water electrolysis, comprising the following steps:
[0052] 8 mL of DMF was used as solvent, 1.2 g of PAN, 2 g of SAN, 5 mmol of copper nitrate, 5 mmol of tin chloride, and finally 1 g of PVP were added. After uniform dissolution, an electrospinning reaction solution was obtained. The electrospinning reaction solution was loaded into a Luer lock syringe, and the electrospinning voltage was set to 17 kV, the distance between the nozzle and the aluminum foil was set to 15 cm, and the injection pump pressing speed was set to 1 mL·h -1 , coaxial electrospinning was performed; the electrospun product and an appropriate amount of nickel foam were placed in a muffle furnace under an inert atmosphere of Ar at 4 °C·min -1 The temperature was raised to 700 °C and calcined for 4 h to obtain a Cu-Sn bimetallic catalyst with a loading of 5 mg / cm 2 Active ingredient;
[0053] Figure 2 The scanning electron microscope image of the Cu-Sn bimetallic catalyst in Example 2 is shown in Figure 1, which is magnified 15,000 times. It can be seen that the catalyst has a finger-like protrusion structure, indicating that Pd can regulate the microstructure of the catalyst. The electron paramagnetic resonance test of Example 1 and Example 2 was sent to "Hua Xun Computing" for testing. The specific test results are shown in Figure 1. Figure 3 ,from Figure 3 It can be seen that compared with Example 2, Example 1 shows a strong characteristic peak at g=2.007, indicating that the catalyst in Example 1 has abundant oxygen vacancies, indicating that the introduction of Pd into Cu-Sn can further change the electronic structure and induce the generation of oxygen vacancies, which is more conducive to improving the activity of the catalyst.
[0054] Example 3
[0055] This embodiment provides a method for preparing a Cu-Sn bimetallic catalyst for water electrolysis, comprising the following steps:
[0056] 10 mL of DMF was used as solvent, 1.5 g of PAN, 3 g of SAN, 6 mmol of copper nitrate, 4 mmol of tin chloride and 2 mmol of palladium nitrate were added, and finally 4 g of PVP was added. After being dissolved evenly, an electrospinning reaction solution was obtained. The electrospinning reaction solution was loaded into a Luer lock syringe, and the electrospinning voltage was set to 10 kV, the distance between the nozzle and the aluminum foil was set to 10 cm, and the injection pump pressing speed was set to 0.5 mL·h -1 , coaxial electrospinning was performed; the electrospun product and an appropriate amount of nickel foam were placed in a muffle furnace, and heated at 2°C·min in an inert atmosphere of Ar. -1 The temperature was raised to 1200℃ and calcined for 2h to obtain a Cu-Sn bimetallic catalyst with a loading of 5mg / cm 2 Active ingredient.
[0057] Example 4
[0058] This embodiment provides a method for preparing a Cu-Sn bimetallic catalyst for water electrolysis, comprising the following steps:
[0059] 6 mL of DMF was used as solvent, 2.5 g of PAN, 2 g of SAN, 4 mmol of copper nitrate, 6 mmol of tin chloride, 2 mmol of palladium nitrate, and finally 2 g of PVP were added. After uniform dissolution, an electrospinning reaction solution was obtained. The electrospinning reaction solution was loaded into a Luer lock syringe, and the electrospinning voltage was set to 30 kV, the distance between the nozzle and the aluminum foil was set to 20 cm, and the injection pump pressing speed was set to 6 mL·h -1 , coaxial electrospinning was performed; the electrospun product and an appropriate amount of nickel foam were placed in a muffle furnace under an inert atmosphere of Ar at 6 °C·min -1 The temperature was raised to 500 °C and calcined for 10 h to obtain a Cu-Sn bimetallic catalyst with a loading of 5 mg / cm 2 Active ingredient.
[0060] Example 5
[0061] This embodiment provides a method for preparing a Cu-Sn bimetallic catalyst for water electrolysis, comprising the following steps:
[0062] 4 mL of DMF was used as solvent, 0.5 g of PAN, 0.1 g of SAN, 6 mmol of copper nitrate, 7 mmol of tin chloride and 3 mmol of palladium nitrate were added, and finally 0.4 g of PVP was added. After uniform dissolution, an electrospinning reaction solution was obtained. The electrospinning reaction solution was loaded into a Luer lock syringe, and the electrospinning voltage was set to 25 kV, the distance between the nozzle and the aluminum foil was set to 17 cm, and the injection pump pressing speed was set to 3 mL·h -1, coaxial electrospinning was performed; the electrospun product and an appropriate amount of nickel foam were placed in a muffle furnace, and heated at 8 °C·min in an inert atmosphere of Ar. -1 The temperature was raised to 1000℃ and calcined for 7h to obtain a Cu-Sn bimetallic catalyst with a loading of 5mg / cm 2 Active ingredient.
[0063] Example 6
[0064] This embodiment provides a method for preparing a Cu-Sn bimetallic catalyst for water electrolysis, comprising the following steps:
[0065] 2 mL of DMF was used as solvent, 4 g of PAN, 4 g of SAN, 2 mmol of copper nitrate, 8 mmol of tin chloride and 4 mmol of palladium nitrate were added, and finally 2 g of PVP was added. After being uniformly dissolved, an electrospinning reaction solution was obtained. The electrospinning reaction solution was loaded into a Luer lock syringe, and the electrospinning voltage was set to 12 kV, the distance between the nozzle and the aluminum foil was set to 12 cm, and the injection pump pressing speed was set to 2 mL·h -1 , coaxial electrospinning was performed; the electrospun product and an appropriate amount of nickel foam were placed in a muffle furnace, and heated at 3℃·min in an inert atmosphere of Ar. -1 The temperature was raised to 800 °C and calcined for 6 h to obtain a Cu-Sn bimetallic catalyst with a loading of 5 mg / cm 2 Active ingredient.
[0066] Example 7
[0067] This embodiment provides a method for preparing a Cu-Sn bimetallic catalyst for water electrolysis, comprising the following steps:
[0068] 3 mL of DMF was used as solvent, 1 g of PAN, 1 g of SAN, 2 mmol of copper acetate, 2 mmol of tin methanesulfonate and 1 mmol of palladium chloride were added, and finally 1 g of PVP was added. After uniform dissolution, an electrospinning reaction solution was obtained. The electrospinning reaction solution was loaded into a Luer lock syringe, and the electrospinning voltage was set to 23 kV, the distance between the nozzle and the aluminum foil was set to 13 cm, and the injection pump pressing speed was set to 5 mL·h -1 , coaxial electrospinning was performed; the electrospun product and an appropriate amount of nickel foam were placed in a muffle furnace, and heated at 5℃·min in an inert atmosphere of Ar. -1 The temperature was raised to 600 °C and calcined for 3 h to obtain a Cu-Sn bimetallic catalyst with a loading of 5 mg / cm 2 Active ingredient.
[0069] Example 8
[0070] This embodiment provides a method for preparing a Cu-Sn bimetallic catalyst for water electrolysis, comprising the following steps:
[0071] The method of Example 5 was followed except that the electrospinning voltage was set to 25 kV, the distance between the nozzle and the aluminum foil was set to 17 cm, and the injection pump speed was set to 3 mL·h -1 " was changed to "The electrospinning voltage was 40 kV, the distance between the nozzle and the aluminum foil was 5 cm, and the injection pump speed was 8 mL·h -1 ”.
[0072] Example 9
[0073] This embodiment provides a method for preparing a Cu-Sn bimetallic catalyst for water electrolysis, comprising the following steps:
[0074] The method of Example 6 is the same as that of Example 6, except that the temperature is set at 3 °C·min -1 The temperature was raised to 800℃ and calcined for 6h at a rate of 1℃·min -1 The temperature was raised to 300°C and calcined for 1h.
[0075] Comparative Example 1
[0076] This comparative example provides a method for preparing a catalyst for electrolysis of water, comprising the following steps:
[0077] The method of Example 1 is followed, except that “5 mmol of copper nitrate, 5 mmol of tin chloride and 1 mmol of palladium nitrate” is replaced by “10 mmol of tin chloride and 1 mmol of palladium nitrate”.
[0078] Comparative Example 2
[0079] This comparative example provides a method for preparing a catalyst for electrolysis of water, comprising the following steps:
[0080] The method of Example 1 is followed, except that “5 mmol of copper nitrate, 5 mmol of tin chloride and 1 mmol of palladium nitrate” is replaced by “10 mmol of copper nitrate and 1 mmol of palladium nitrate”.
[0081] Comparative Example 3
[0082] This comparative example provides a method for preparing a Cu-Sn bimetallic catalyst for water electrolysis, comprising the following steps:
[0083] The method of Example 4 is followed, except that "4 mmol of copper nitrate, 6 mmol of tin chloride and 2 mmol of palladium nitrate" is changed to "1 mmol of copper nitrate, 9 mmol of tin chloride and 5 mmol of palladium nitrate".
[0084] Test Case
[0085] Water electrolysis hydrogen production performance test: The electrochemical hydrogen evolution performance of the catalyst was tested using a standard three-electrode electrochemical workstation (CHI 760e), with a test area of 1 cm 2 The nickel foam loaded with catalyst was used as the working electrode, the platinum sheet was used as the counter electrode, the Hg / HgO electrode was used as the reference electrode, and the electrolyte was a KOH solution with a concentration of 1 mol / L. In the voltage range of 0-2 V, the reaction was carried out at a rate of 2 mV·s -1 The polarization curve was measured at the scanning rate, and the results of the hydrogen production performance of water electrolysis after iR correction are shown in Table 1.
[0086] Table 1
[0087]
[0088] Note: HER overpotential (-10mA·cm -2 ) The overpotential in mV is a vector value, with the negative sign indicating the direction.
[0089] The overpotential represents the overpotential exhibited by the electrode of each embodiment when performing the electrolysis of water to generate hydrogen at a specific current density. The overpotential is the potential difference relative to the standard hydrogen electrode (SHE), which reflects the additional voltage required to maintain a specific current density in the actual electrode reaction.
[0090] The higher the overpotential, the greater the resistance of the electrode reaction, and a higher voltage needs to be applied to maintain the same current density. In the process of electrolysis of water to produce hydrogen, the overpotential is one of the important indicators to measure the performance of the electrode. The lower the overpotential, the better the catalytic performance of the electrode and the easier the reaction process is.
[0091] Combination Figure 4 and Figure 5 The iRs-corrected LSV curve and Table 1 show that the catalyst in Example 1 can reach 100 mA cm in the OER reaction when the overpotential (overpotential is the test voltage minus the OER standard potential 1.23 V) is only 270 mV. -2 In the HER reaction, when the overpotential is only 98 mV, the current density can reach -10 mA cm -2 of current density.
[0092] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing a Cu-Sn bimetallic catalyst for water electrolysis, characterized in that: The preparation method comprises the following steps: A copper-containing precursor, a tin-containing precursor, a palladium-containing precursor, a spinning material and a solvent are mixed, and electrospinning is performed, and the electrospinning product is placed on a substrate for calcination to obtain a Cu-Sn bimetallic catalyst for water electrolysis; Wherein, the molar ratio of the copper element in the copper-containing precursor, the tin element in the tin-containing precursor, and the palladium element in the palladium-containing precursor is (5-7):(5-7):(1-3); The calcination conditions include: 1-8 ° C. min -1 The temperature is raised to 300-1200°C and calcined for 1-10h.
2. The preparation method according to claim 1, characterized in that: The ratio of the copper element to the spinning material in the copper-containing precursor is (5-7) mmol: (0.5-10) g.
3. The preparation method according to claim 1, characterized in that: The copper-containing precursor is a soluble copper salt; and / or, the tin-containing precursor is a soluble tin salt; and / or, the palladium-containing precursor is a soluble palladium salt; And / or, the spinning material includes polyacrylonitrile.
4. The preparation method according to claim 3, characterized in that: The soluble copper salt includes at least one of copper nitrate, copper acetate, copper chloride and copper sulfate; And / or, the soluble tin salt includes at least one of tin alkyl sulfonate and tin chloride; And / or, the soluble palladium salt comprises at least one of palladium chloride and palladium nitrate; And / or, the spinning material further comprises at least one of styrene-acrylonitrile copolymer and polyvinyl pyrrolidone.
5. The preparation method according to claim 4, characterized in that: The mass ratio of the polyacrylonitrile, styrene-acrylonitrile copolymer and polyvinyl pyrrolidone is (0.5-4):(0.1-4):(0.1-4).
6. The preparation method according to claim 1, characterized in that: The parameters of the electrospinning include: voltage of 10-40 kV, distance between nozzle and collector of 5-20 cm, injection pump pressing speed of 0.5-10 mL·h -1 ; And / or, the calcination conditions include: 2-6°C·min -1 The temperature is raised to 500-800°C and calcined for 2-8h.
7. The preparation method according to claim 6, characterized in that: The voltage is 15-30 kV, the distance between the nozzle and the collector is 10-15 cm, and the injection pump pressing speed is 3-6 mL·h -1 .
8. A Cu-Sn bimetallic catalyst for water electrolysis obtained by the preparation method according to any one of claims 1 to 7.